Role of Novel Drug Delivery Vehicles in Nanobiomedicine - Tyagi, Rajeev K.; Garg, Neeraj; Shukla, Rahul; Singh Bisen, Prakash (IntechOpen, 2020)
Medical Nanotechnology and Nanomedicine introduces non-experts to the world of nanomedicine and its evolving organizational infrastructure. Considering the fluid nature of nano breakthroughs and the delicate balance between benefits and consequences as they apply to medicine, readers at all levels will gain a practical, understandable base of information on these developments so that they may take the greatest advantage of them. This practical reference investigates the impact of nanotechnology on applications in medicine and biomedical sciences, and the broader societal and economic effects. Eschewing technological details, it focuses on enhancing awareness of the business, regulatory, and administrative aspects of medical applications. It gives readers a critical, balanced, and realistic evaluation of existing nanomedicine developments and future prospects and provides an ideal foundation upon which to plan and make decisions.